DEVELOPING VIEWS ON DISCURSIVE ANALYSIS - Khusanova Indira Akbardjanovna (American Journals Publishing, 2024)
This article aims to delve into the various perspectives surrounding discursive analysis, including its theoretical foundations, methodological approaches, and its significance in comprehending social phenomena. Additionally, we will examine the obstacles and critiques faced by discursive analysis, and propose potential avenues for its advancement in addressing these concerns.
Keywords: Practical applications, discursive practices, social practices, methodological approaches, practical implementations, communication practices, including vocabulary, grammar, syntax, rhetorical devices